OPPORTUNISTIC APPROACH TO EXPLOIT WIRELESS SPECTRUM BY USE OF COGNITIVE RADIO - Preet, Tanu Preet Singh; Singh, Prof. R.K; Kaur, Jaspreet; Sharma, Vishal (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Cognitive radio (CR) technology is envisaged to solve the problems in wireless networks resulting from the limited available spectrum and the inefficiency in the spectrum usage by exploiting the existing wireless spectrum opportunistically. In this paper, intrinsic properties and research on software defined cognitive radio (SDCR) are presented. Firstly brief introduction of Cognitive Radio is given along with its architecture.Â Then spectrum management of Cognitive Radio ad hoc networks (CRAHNs) and their main features like spectrum sensing, spectrum decision, spectrum selection and spectrum mobility are defined. At the end, Software Defined Cognitive Radio (SDCR), its hardware and software platform, along with research topics on SDCR are defined